Amino Acid, Phytochemical Compositions and Antioxidant Activity of Inky Cap Mushroom (Coprinus radiata) - Somdee, Thidarat; Kraiklang, Rattaphol; Mahaweerawat, Chatchada; Yangyuen, Suneerat; Mahaweerawat, Udomsak; Chumroenphat, Theeraphan; Somdee, Theerasak (Asian Journal of Chemistry, 2020)
Evaluation of the amino acid composition, phytochemical properties and antioxidant activity of Coprinus radiata mushrooms was conducted. Free amino acid composition of fresh mushrooms was analyzed by LC-MS/MS. The phytochemical properties analysis included total phenolic compound content and total flavonoid content of these mushrooms. Furthermore, antioxidant activity assays were performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP). Based on the results shown that a high concentration of non-essential amino acids, especially those of arginine and glutamic acid, were observed. However, isoleucine and leucine were major essential amino acids in these mushrooms. The ethanolic extract of C. radiata showed higher phytochemical contents and antioxidant activity than those of the water extract. It suggested that the C. radiata is a natural source containing some essential amino acids, a high amount of phytochemical properties and high antioxidant activity, potentially having medicinal and nutritional properties that provide health benefits.